2016
DOI: 10.1007/s10493-016-0031-8
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal changes in the fatty acid profile of the tick Ixodes ricinus (Acari, Ixodidae)

Abstract: Fatty acids (FAs) from nymphs, females and males of Ixodes ricinus were analysed by gas chromatography/mass spectrometry. Ticks were collected from May to October 2013. The most abundant FAs were 18:1, 18:0, 16:0 and 18:2 which are also dominant FAs of insects. Adults contained higher concentrations of FAs in general than nymphs because they contain more fat body and probably a thicker layer of epicuticular lipids. Larger quantities of FAs > 20 carbon atoms in the carboxylic chain were present in females, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…This strategy may improve resistance to starvation (e.g., Pincheira-Donoso et al 2008 ). For example, Cuber et al ( 2016 ) observed that the fatty acid profile of Ixodes ricinus ticks varied significantly from season to season, and their content tended to increase at lower temperatures. The ameronothrid mite Alaskozetes antarcticus exhibits a similar pattern of rapid growth during a brief summer period, resulting in large bodies at the beginning of winter (Convey 1994 ).…”
Section: Discussionmentioning
confidence: 99%
“…This strategy may improve resistance to starvation (e.g., Pincheira-Donoso et al 2008 ). For example, Cuber et al ( 2016 ) observed that the fatty acid profile of Ixodes ricinus ticks varied significantly from season to season, and their content tended to increase at lower temperatures. The ameronothrid mite Alaskozetes antarcticus exhibits a similar pattern of rapid growth during a brief summer period, resulting in large bodies at the beginning of winter (Convey 1994 ).…”
Section: Discussionmentioning
confidence: 99%